1980
DOI: 10.1159/000241261
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Transplacental Passage of ACTH in the Rat: Direct Experimental Proof

Abstract: In order to investigate whether ACTH can cross the placenta of the rat at term, porcine 125I-ACTH was injected into mothers or fetuses. ACTHwas then extracted from maternal and fetal plasma, using QUSO G-32, 2.5, 5, 10, 15 and 20 min after the injection of labelled ACTH. Plasma samples were also chromatographed on Sephadex G-50, fine, columns, 5 and 20 min after the administration of ACTH. When 125I-ACTH was injected into the mothers, the two methods used were unable to detect any radioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

1981
1981
2004
2004

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…Also, there are some lines of evidence that the hypothalamus begins to control the pituitary-adrenal system before birth [5,10,11,16], though evidence indi cates that the onset of the hypothalamic con trol occurs slightly later than that of the pitu itary regulation of the adrenal [9], Adrenalectomy of pregnant rats results in a hypertrophy of the fetal adrenals near the end of gestation and just after birth [21], a phenomenon which is considered a compen satory event in the fetus owing to maternal adrenocortical deficiency. In relation to this, it will be pertinent to mention that maternal ACTH cannot cross the placenta [7], but cor ticoids can [1,6], Thus, the compensatory hypertrophy of fetal adrenals after maternal adrenalectomy is interpreted as a result of the negative feedback response of the fetal pitu itary-adrenal system to the declined amount of fetal circulating corticoids derived from the mother. Fetal unilateral adrenalectomy causes a significant hypertrophy of the fetal contralateral adrenal at the end of gestation as well [8], a phenomenon which is also con sidered a result of the fetal pituitary-adrenal feedback response.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there are some lines of evidence that the hypothalamus begins to control the pituitary-adrenal system before birth [5,10,11,16], though evidence indi cates that the onset of the hypothalamic con trol occurs slightly later than that of the pitu itary regulation of the adrenal [9], Adrenalectomy of pregnant rats results in a hypertrophy of the fetal adrenals near the end of gestation and just after birth [21], a phenomenon which is considered a compen satory event in the fetus owing to maternal adrenocortical deficiency. In relation to this, it will be pertinent to mention that maternal ACTH cannot cross the placenta [7], but cor ticoids can [1,6], Thus, the compensatory hypertrophy of fetal adrenals after maternal adrenalectomy is interpreted as a result of the negative feedback response of the fetal pitu itary-adrenal system to the declined amount of fetal circulating corticoids derived from the mother. Fetal unilateral adrenalectomy causes a significant hypertrophy of the fetal contralateral adrenal at the end of gestation as well [8], a phenomenon which is also con sidered a result of the fetal pituitary-adrenal feedback response.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, direct experimental evidence indicates the lack of a transplacental passage of 125 I-ACTH from the pregnant rat to the fetus as well as from the fetus to the mother (Dupouy et al, 1980). In the human placenta, the expression of corticotropin-releasing factor (CRF) increases as much as 100 times during the last 6 to 8 weeks of pregnancy and is paradoxically stimulated by glucocorticoids (Majzoub and Karalis, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research demonstrated that alcohol consumption increases plasma corticosterone levels in the dams [7, 22], and that this glucocorticoid can cross the placenta and influence the development of the fetal HPA axis [23]. Furthermore, maternal ADX has been shown to prevent various effects of FAE on the HPA axis.…”
Section: Discussionmentioning
confidence: 99%